Pendidikan Karakter di Asrama 2 PGSD UNNES Ngaliyan - Afdhilla, Nisa; Nurharini, Atip; Lituhayu, Garini; Rosyidah, Ummi; Stevano, Marshelino (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Character education is an important aspect that must be considered in forming individuals who are not only intellectually intelligent, but also have high moral and social integrity. In the context of higher education, especially in student dormitories, character education becomes increasingly important considering that dormitories are places where students spend most of their time and interact intensively with fellow residents. Semarang State University (UNNES) as one of the teacher education institutions in Indonesia, has a strategic role in producing prospective educators with character. Dormitory 2 PGSD UNNES Ngaliyan, with the vision of creating a healthy, superior and prosperous life, is committed to activating a character building and development program that trains independence, sensitivity, responsibility and leadership. This study used qualitative research methods. This qualitative approach is used to describe and analyze individual or group phenomena, events, social dynamics, attitudes, beliefs and perceptions. The research was carried out by means of observation and interviews containing questions for related parties according to the topic raised by the author. The results of this research are regarding the method used in the process of cultivating character in Dormitory 2 PGSD UNNES Ngaliyan, namely by creating regulations that the dormitory residents must adhere to and holding various kinds of activities involving the dormitory participants. In Dormitory 2 PGSD UNNES Ngaliyan activities there are various kinds of activities, namely in terms of spirituality there are mandatory congregational prayers for Muslims and Sunday worship for non-Muslims, activities for the Prophet's birthday, halal bihalal, and so on.